4D flow imaging with UNFOLD in a reduced FOV. Issue 1 (24th December 2019) - Wink, Clarissa; Bassenge, Jean Pierre; Ferrazzi, Giulio; Schaeffter, Tobias; Schmitter, Sebastian
Abstract : Purpose: Two‐dimensional selective excitation (2DRF) allows shortening 4D flow scan times by reducing the FOV, but the longer 2DRF pulse duration decreases the temporal resolution, yielding underestimated peak flow values. Multiple k‐space lines per cardiac phase, n l ≥ 2, are commonly applied in 4D flow MRI to shorten the inherent long scan times. We demonstrate that 2DRF 4D flow with n l ≥ 2 can be easily combined with UNFOLD (UNaliasing by Fourier‐encoding the Overlaps using the temporaL Dimension), a technique that allows regaining nominally the temporal resolution of the respective acquisition with n l = 1, to assure peak flow quantification. Methods: Two different 2DRF pulses with spiral k‐space trajectories were designed and integrated into a 4D flow sequence. Flow phantom experiments and 7 healthy control 4D flow in vivo measurements, with and without UNFOLD reconstructions, were compared with conventional reconstruction and 1D slab‐selective excitation (1DRF) by evaluating time‐resolved flow curves, peak flow, peak velocity, blood flow volume per cardiac cycle, and spatial aliasing. Results: Applying UNFOLD to 4D flow imaging with 2DRF and reduced FOV increased the quantified in vivo peak flow values significantly by 3.7% ± 2.3% to 5.2% ± 2.4% ( P < .05). Accordingly, the peak flow underestimation of 2DRF scans compared with conventional 1DRF scans decreased with UNFOLD. Finally, 2DRF combined with UNFOLD accelerated the 4D flow acquisition 3.5 ± 1.4 fold by reducing the FOV and increasing the effective temporal resolution by 6.7% compared with conventional 1D selective excitation, with 2 k‐space lines per cardiac phase. Conclusion: Two‐dimensional selective excitation combined with UNFOLD allows limiting the FOV to shorten 4D flow scan times and compensates for the loss in temporal resolution with 2DRF (Δ t = 64.8 ms) compared with 1DRF (Δ t = 43.2 ms), yielding an effective resolution of Δ t eff = 40.5 ms to enhance peak flow quantification.